The Grammatical Term in the Modern Al-Khalilist Theory of Abdul Rahman al-Hajj Saleh - بلحاجي, فتيحة; وهيب , وهيبة (Milev Journal of Research and Studies, 2023)
The modern Al-Khalilist theory of Abdul Rahman Al Haj Saleh is considered to be one of the leading modern linguistic theories in the Arab world; its aim is to reconcile the development of ancient Arab linguistic heritage thought with the latest linguistic concepts of contemporary Western linguistics. Most of the concepts and principles in this theory date back to The Book of Sibawayh and the grammar books that followed the model of the book, as well as the most important Arabic works compilled until the 4th century AH. The theorist relied on an arsenal of grammatical terms in his study and analysis of the linguistic phenomenon, such as integrity, initiation and separation, the factor and other heritage terms in which he approached modern linguistic concepts. We therefore intend to present a research paper in which we inquire about the most important of these terms, while clarifying the faces of their authenticity or renewal.